2022
DOI: 10.3389/fsufs.2022.832896
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking PGPR-Mediated Abiotic Stress Tolerance: What Lies Beneath

Abstract: In the forthcoming era of climate change and ecosystem degradation, fostering the use of beneficial microbiota in agroecosystems represents a major challenge toward sustainability. Some plant-associated bacteria, called Plant Growth Promoting Rhizobacteria (PGPR), may confer growth-promoting advantages to the plant host, through enhancing nutrient uptake, altering hormone homeostasis, and/or improving tolerance to abiotic stress factors and phytopathogens. In this regard, exploring the key ecological and evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 60 publications
(105 reference statements)
0
24
0
Order By: Relevance
“…Application of plant growth‐promoting rhizobacteria (PGPRs) into the soil needs certain requirements that fulfil appropriate carriers, shelf‐life and sustainability of the rhizobacteria in the field. The key challenges for the universal application of the PGPR include storage incompatibility, short shelf‐life, inconsistent field performance and delicate application techniques required in field conditions (Mellidou & Karamanoli, 2022). The capability of the organism for efficient root colonization and generating positive response in host plant depends on plant–microbe interactions and soil factors (Hussain et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Application of plant growth‐promoting rhizobacteria (PGPRs) into the soil needs certain requirements that fulfil appropriate carriers, shelf‐life and sustainability of the rhizobacteria in the field. The key challenges for the universal application of the PGPR include storage incompatibility, short shelf‐life, inconsistent field performance and delicate application techniques required in field conditions (Mellidou & Karamanoli, 2022). The capability of the organism for efficient root colonization and generating positive response in host plant depends on plant–microbe interactions and soil factors (Hussain et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…enhanced resistance to pathogens in Arabidopsis , whereas Kang et al (2022) demonstrated that PGPB aids in improving plant growth and nitrogen use efficiency. PGPB helps plants combat salt stress by regulating antioxidants, ion balance, and stress pathways like HKT and SOS and inducing ABA and indole acetic acid (IAA) to protect against drought stress (Mellidou and Karamanoli, 2022). In this study, we employed biochemical and genomic approaches to evaluate the potential of Pseudomonas koreensis strain S4T10 for enhancing the growth of Arabidopsis seedlings exposed to extended drought and salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Current research on crop rhizospheres reveals the frequent presence of Pseudomonas species that serve as potential PGPB (Ofek et al, 2014, Walters et al, 2018, Chiniquy et al, 2021. van (Mellidou and Karamanoli, 2022). In this study, we employed biochemical and genomic approaches to evaluate the potential of Pseudomonas koreensis strain S4T10 for enhancing the growth of Arabidopsis seedlings exposed to extended drought and salt stress.…”
mentioning
confidence: 99%
“…This is primarily due to the mode of selection process wherein PGP traits of microbes are assessed at a laboratory scale under highly controlled conditions, while field conditions are markedly different (Vasseur-Coronado et al, 2021). In fields, multiple factors interact, hence the PGP potentials of microbes are often lost or masked leading to underperformance (Backer et al, 2018;Mellidou and Karamanoli, 2022). Hence, the selection of the right microbe which does not lose its PGP traits under field conditions and various stresses is crucial (Amaya-Goḿez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%